Nonlinear differential equations with neutral term: Asymptotic behavior of solutions - Maryam AlKandari (AIMS Mathematics)
The aim of this work is to study some oscillation behavior of solutions of a class of third-order neutral differential equations with multi delays. We present new oscillation criteria that complete and simplify some previous results. We also provide an example to clarify the significance of our results.